Jeprut: Perlawanan terhadap Hegemoni Kekuasaan - Ipit Dimyati (Antropologi Indonesia, 2004)
Jeprut is a well-known art performance in Bandung. Its form is unusual because Jeprut does not follow the usual norms in arts performance. Therefore, sometimes its existence is not recognized as an art, but rather as a compensation for people who are not competent enough to deliver an art performance. Jeprut artists are actually conducting an indirect resistance towards the New Order's authority. There are two resistance movements showing by the Jeprut. First is the external, by doing resistance to the political situation and the second is an internal resistance, by which Jeprut is conducting a resistance towards art's existence during the New Order's regime. A study about Jeprut is confirming that an art's definition cannot be determined by only its internal aspects but also by its external ones. It means that something cannot be defined as arts just by its own existence but also by some power.